Ice flow modelling to constrain the surface mass balance and ice discharge of San Rafael Glacier, Northern Patagonia Icefield - Collao-Barrios, Gabriela; Gillet-Chaulet, Fabien; Favier, Vincent; Casassa, Gino; Berthier, Etienne; Dussaillant, Ines; Mouginot, Jeremie; Rignot, Eric (My University, 2018)
We simulate the ice dynamics of the San Rafael Glacier (SRG) in the Northern Patagonia Icefield (46.7 degrees S, 73.5 degrees W), using glacier geometry obtained by airborne gravity measurements. The full-Stokes ice flow model (Elmer/Ice) is initialized using an inverse method to infer the basal friction coefficient from a satellite-derived surface velocity mosaic. The high surface velocities (7.6 km a(-1)) near the glacier front are explained by low basal shear stresses (<25 kPa). The modelling results suggest that 98% of the surface velocities are due to basal sliding in the fast-flowing glacier tongue (>1 km a(-1)). We force the model using different surface mass-balance scenarios taken or adapted from previous studies and geodetic elevation changes between 2000 and 2012. Our results suggest that previous estimates of average surface mass balance over the entire glacier (B.) were likely too high, mainly due to an overestimation in the accumulation area. We propose that most of SRG imbalance is due to the large ice discharge (-0.83 +/- 0.08 Gt a(-1)) and a slightly positive B. (0.08 +/- 0.06 Gt a(-1)). The committed mass-loss estimate over the next century is -0.34 +/- 0.03 Gt a(-1). This study demonstrates that surface mass-balance estimates and glacier wastage projections can be improved using a physically based ice flow model.
Keywords: glacier modelling; ice dynamics; surface mass budget